Scalable ergothioneine production via integrating chemical methylation and rhodanese-catalyzed CS bond formation - Jie Lu; Xiaoyuan Sun; Hanzhi Weng; Weiquan Ding; Fengling Yang; Guochen Du; Ruirui Xu; Zhen Kang (Chemical Engineering Journal, 2026)

Data-Driven Insights and Prediction of Bauxite-Hosted Lithium Mineralization - Xiaokang Liang; Guotao Sun; Yong Fu; Bo Tang; Peiwen Chen; Zaiping Shi; Shijiang Yang; Guochen Zhou; Zhonghong Huang; Qiaolin Fu; Tianyi Liu (Natural Resources Research, 2026)

Origin of granitic pegmatites: Perspectives from elements and Li Hf isotopes, Chakabeishan, northern Tibetan Plateau - Wenli Sun; Zhidan Zhao; Xuanxue Mo; Guochen Dong; Xiaowei Li; Wanming Yuan; Tao Wang; Bingzhang Wang; Tong Pan; Jie Han; Yan Tang; Ningyuan Qi; et al. (Lithos, 2025)

Design and testing of the clam vibration harvester's V-shaped double-spiral harvesting roller brush based on DEM-MBD - Li Hangqi; Mu Gang; Li Xiuchen; Wu Hao; Xu Bin; Liu Fawei; Sun Zhenyin; Zhang Qian; Zhang Hanbing; Xin Mingjin; Zhang Guochen (Aquacultural Engineering, 2025)

Genomic Adaptation of Marine Medaka ( Oryzias melastigma ) Under Artificial Life‐History Selection - Peng Sun; Guochen Gan; Yongjun Tian; Zhenlin Liang; Yujia Yang; Mikko Heino (Molecular Ecology, 2025)
Size‐selective harvesting imposes indirect selection on life‐history traits and has profound evolutionary and ecological implications for fish populations, influencing traits such as body size, reproductive success, hatchability, and driving significant genetic shifts. Here, we investigated the long‐term effects of three harvesting strategies, large‐harvested (LH), small‐harvested (SH), and random‐harvested (RH), on marine medaka ( Oryzias melastigma ) populations over five generations. We observed declines in body length and weight in the LH group, whereas these traits increased in the SH group, with the RH group remaining relatively stable. In terms of hatchability, SH surpassed LH but remained below RH. Genome‐wide analyses identified key selective regions on chromosomes 8, 13, and 21, which were associated with growth and reproductive fitness. Genome‐wide association studies (GWAS) identified significant loci on chromosome 13 linked to genes such as fat3a , kcnj13 , and gucy1a2 , which are strongly correlated with body weight. These findings suggest a close link between selective harvesting and life‐history evolution, indicating that fishing behaviour may drive genetic shifts within populations. Furthermore, our results imply that selective pressures could influence phenotypic traits and allele frequencies, potentially leading to long‐term or even irreversible genetic changes that might affect growth and survival, traits important for population sustainability.

Zircon chemistry of the late cretaceous-eocene granites from Tengchong block: insights into the genesis of host magmas - Zhuanrong Sun; Guochen Dong; Jianheng Guo; Zhongbao Wang (Mineralogy and Petrology, 2025)

Size-Selective Harvesting Effects on Reproductive Investment in Marine Medaka (Oryzias melastigma) - Guochen Gan; Guankui Liu; Xinyao Sun; Wenbo Deng; Fengming Lv; Yongjun Tian; Peng Sun (Fishes, 2025)
Long-term selective fishing pressure often leads to miniaturization, smaller size, and early sexual maturity in many commercial fish species. To adapt, these species increase energy allocations toward maturation and reproduction, which can reduce population productivity and recruitment. However, how different fishing pressures affect reproductive investment and energy allocation between growth and reproduction remains unclear. In this study, we designed three size-selective harvesting strategies—large, random, and small harvests—to examine their effects on the growth and reproductive investment of marine medaka (Oryzias melastigma). We analyzed changes in length, weight, and gonad weight across different harvest times. Results showed that the “large harvest” group allocated more energy to reproduction, leading to miniaturization and earlier maturation, while the “small harvest” group focused more on growth, resulting in larger fish at the same age. This study provides experimental evidence on how size-selective harvesting alters reproductive investment in fish populations, offering valuable insights for the sustainable exploitation of fishery resources.

Energy-locking-loop: Heterogeneous gel interphase potential enhances battery performance - Meizhi Li; Miao Sun; Guochen Ji; Junping Zheng (Chemical Engineering Journal, 2025)

Bioorthogonal click chemistry and aptamer-targeting enables highly selective fluorescence labeling of exosomal glycosylated EpCAM for super resolved imaging - Zichun Li; Yifan Liu; Feiran Liu; Guochen Sun; Xiaoling Zhang; Jing Jing (Analytica Chimica Acta, 2025)

Transpiration and water use sources of poplar (Populus × xiaozhuanica) plantations with 7-years vs. 20-years old in a semiarid sandy region of Northeast China - Lining Song; Jiaojun Zhu; Xin Liu; Jinxin Zhang; Xiao Zheng; Yirong Sun; Guochen Wang; Linyou Lü (Agricultural and Forest Meteorology, 2024)

Jurassic–cretaceous exhumation history of the Northern Qaidam Basin and its implications for Northeastern Qinghai–Tibet plateau tectonism: evidences from zircon fission track thermochronology - Zirui Feng; Wanming Yuan; Zhidan Zhao; Guochen Dong; Xiaowei Li; Wenli Sun; Li Yang; Shujiong Hong; Mingming Zhao; Caixia Hu; Shiyu Li (International Geology Review, 2024)

Apatite chemistry of Late Triassic granitic rocks from Yidun Terrane: Implications for petrogenesis and mineralization - Zhuanrong Sun; Guochen Dong; Jiahui Tang; Jianheng Guo; Zhongbao Wang (Mineralogy and Petrology, 2023)

Mesozoic–Cenozoic cooling, exhumation and tectonic implications of Chaqiabeishan–Shaliuquan Li Be ore district in the northeastern Qinghai–Tibet Plateau - Zirui Feng; Wanming Yuan; Zhidan Zhao; Guochen Dong; Xiaowei Li; Wenli Sun; Li Yang; Shujiong Hong; Mingming Zhao; Caixia Hu; Shiyu Li (Tectonophysics, 2023)

Vitamin B ameliorates PM2.5-induced kidney damage by reducing endoplasmic reticulum stress and oxidative stress in pregnant mice and HK-2 - Chunming Xu; Qian Zhang; Guochen Huang; Jia Huang; Xiaoyan Fu; Meifang Liu; Yonghong Sun; Hongxia Zhang (Toxicology, 2023)

A hydrogel electrolyte with ultrahigh ionic conductivity and transference number benefit from Zn2+ “highways” for dendrite-free Zn-MnO2 battery - Miao Sun; Guochen Ji; Junping Zheng (Chemical Engineering Journal, 2023)

PM2.5-bound polycyclic aromatic hydrocarbons of a megacity in eastern China: Source apportionment and cancer risk assessment - Lian Duan; Huimin Yu; Qiongzhen Wang; Yibo Cao; Guochen Wang; Xueshi Sun; Hao Li; Tian Lin; Zhigang Guo (Science of The Total Environment, 2023)

Design and testing of a mechanized brush-screen cooperative vibration harvester for mudflat-buried shellfish based on the discrete element method - Hangqi Li; Gang Mu; Hanbing Zhang; Hao Wu; Fawei Liu; Zhenyin Sun; Qian Zhang; Yizhou Wang; Yurui Wang; Xiuchen Li; Guochen Zhang (Frontiers in Marine Science, 2023)
Introduction To enhance the application of mechanized harvesting and supplement research on harvesting theory in mudflat-buried shellfish harvesting in China, a brush-screen cooperative mudflat-buried shellfish vibration harvester was designed. Methods The harvester is primarily composed of a crank rocker double-layer vibrating screen, two stage rolling brush, and a conveyor chain. White clams ( Mactra veneriformis ) cultured in mudflats were used as the research objects in this paper, and the mechanics and motion states of the shellfish on the vibrating screen were analyzed. The shellfish harvesting simulation response surface experiments based on the discrete element method (DEM) were conducted to analyze the influence of the main operating parameters on the quantity of shellfish harvested. Results The results revealed that the number of shellfish harvested was significantly influenced ( p < 0.01) by vibrating screen amplitude, first-stage spiral rolling stainless steel brush rotation rate, and harvester travel speed. The optimal combination of key parameters was 1.4 mm, 40 rpm, and 10 m/min, respectively. With these values, the projected shellfish crushing rate was 2.82% and the shellfish harvesting efficiency was 125 pieces/m 2 . The equipment was then manufactured and the shellfish harvesting verification test was performed under the same operating parameters as the simulation. Test results indicated that the harvesting efficiency of the equipment was 114 pieces/m 2 and the shellfish crushing rate was 6.97%. Discussion The shellfish harvesting work could be completed by the equipment effectively and with low loss. The results of this study provide a theoretical reference for a novel mechanized method of harvesting mudflat-buried shellfish.

A modeling approach to the efficient evaluation and analysis of water quality risks in cold zone lakes: a case study of Chagan Lake in Northeast China - Fan Wang; Jianmin Bian; Guochen Zheng; Murong Li; Xiaoqing Sun; Chunpeng Zhang (Environmental Science and Pollution Research, 2022)

Transpiration of Pinus sylvestris var. mongolica trees at different positions of sand dunes in a semiarid sandy region of Northeast China - Lining Song; Jiaojun Zhu; Xinjunyan Li; Kai Wang; Guochen Wang; Haihong Sun (Trees, 2022)

Efficiency of sulfamethoxazole removal from wastewater using aerobic granular sludge: influence of environmental factors - Di Cui; Zeyi Chen; Ximing Cheng; Guochen Zheng; Yuan Sun; Hongna Deng; Wenlan Li (Biodegradation, 2021)

Predicting the near-field strong ground motion based on uncertainties in asperities: an opportunity to reproduce the characteristics of the 1970 Tonghai earthquake (Ms 7.8) - Zongchao Li; Jize Sun; Xueliang Chen; Guochen Wang; Qingfeng Ding (Journal of Seismology, 2021)

Early cretaceous igneous activities in the north flank of the North China Craton: the Shouwangfen complex example - Pengsheng Dong; Guochen Dong; M. Santosh; Zhuanrong Sun; Huawei Li; Shushu Wang; Weiqing Wang (International Geology Review, 2020)